Int flow : aplicação de telemetria em redes definidas por software - Camera, Pedro Eduardo (2019)
Since 2008, Software Defined Networking concepts have gained a lot of attention among computer network engineers and researchers, mainly due to the big flexibility that the concepts bring to network management. This dissertation introduces a new methodology of in-band network telemetry measurements, a framework that collects network status information. For programming the network devices, were used the language Programming Protocolindependent Packet Processors. It’s a language used to define network device behavior and was used to implement the in-band network telemetry method. Most of the in-band network telemetry applications are restrained to data centers environments or simulated ones. The main objective of this work was to use these techniques in hardware to monitor the Metropolitan Area Network. This research applied some in-band network telemetry metrics, like timestamp, flow path, and hop latency. The results obtained demonstrate that the packets sent to the data collector are formatted according to the solution programmed in the data plane, another achievement was that the programmed model allows the capture of data in a network flow. In conclusion, in-band network telemetry flow, the presented final solution, performed monitoring in the lesser granularity of time (milliseconds) than other protocols like simple net